What is Islamic economics? The view of Muhammad Baqir al-Sadr - Hafas Furqani (Jurnal Ekonomi & Keuangan Islam, 2019)
Muhammad Baqir al-Sadr (1935-1980) is a well-known Muslim scholar of the late twentieth century. Al-Sadr is considered as one of the pioneers of Islamic revival in the contemporary Muslim world. His keen intellectual interests inspired him to critically study a wide range of areas in contemporary philosophy, economics, politics, sociology, history and law, from a distinct Islamic point of view. Al-Sadr’s magnum opus on economics, Iqtisaduna (Our Economics) has put his name as one of the pioneers of contemporary Islamic economics. His work, in various degrees has influenced the formation and development of Islamic economics as a system and as a body of knowledge. This paper attempts to investigate some aspects of al-Sadr’s economic thought by focusing on his view on the nature, subject matter and methodology of Islamic economics, areas that have not received sufficient attention by contemporary Islamic economists.